Leverage and Auditor Quality Impact Financial Reporting Timeliness: Evidence from Property and Real Estate Sector: Leverage dan Kualitas Auditor Memengaruhi Kepunctualan Pelaporan Keuangan: Bukti dari Sektor Properti dan Real Estat - Valentino, Fabrisio Handy; Nurasik (Universitas Muhammadiyah Sidoarjo, 2023)
This research investigates the impact of profitability, leverage, firm size, and auditor quality on the timeliness of financial reporting within the property and real estate sector of the Indonesia Stock Exchange for the years 2018 to 2020. Employing logistic regression analysis, our study reveals that leverage and auditor quality significantly influence financial reporting timeliness, while firm size does not exhibit such an effect. These findings contribute to the literature on financial reporting timeliness, offering valuable insights for decision-makers and adding support to prior research efforts in this field. Highlights: Impact of Leverage: Leverage's significant influence on financial reporting timeliness. Auditor Quality Matters: The role of auditor quality in shaping timely financial reporting. Sector-Specific Insights: Findings specific to the property and real estate sector. Keywords: Financial Reporting, Leverage, Auditor Quality, Timeliness, Property and Real Estate Sector